2010
DOI: 10.1002/pbc.22575
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in pediatric patients: Time to think again about surveillance

Abstract: Background. Despite concerns regarding ionizing radiation exposures from diagnostic imaging procedures in pediatric patients, many are deemed unavoidable or even mandated by treatment protocols. A prior review at our institution found patients with lymphoma had a higher median cumulative radiation exposure (191 mSv) versus other oncology subgroups (61 mSv). Purpose. Estimations of cumulative diagnostic radiation exposures were tabulated for 5 years from the first diagnostic scan for 30 consecutive lymphoma pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 41 publications
0
25
1
Order By: Relevance
“…Although some have hypothesized that the majority of the unnecessary surveillance imaging is driven by treatment protocols, a recent study reported that only 34% of 690 imaging procedures performed on patients with lymphoma were protocol required. 20 The remainder of the scans were discretionary investigations; approximately 40% of these surveillance studies were obtained when recurrence risk was low and without an indication in the medical record, emphasizing the need for more thoughtful approach to imaging in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although some have hypothesized that the majority of the unnecessary surveillance imaging is driven by treatment protocols, a recent study reported that only 34% of 690 imaging procedures performed on patients with lymphoma were protocol required. 20 The remainder of the scans were discretionary investigations; approximately 40% of these surveillance studies were obtained when recurrence risk was low and without an indication in the medical record, emphasizing the need for more thoughtful approach to imaging in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of ongoing surveillance imaging remains controversial [9, 12, 13, 17] Chong et al [18] recently reported on the radiation exposure burden placed on survivors of various cancers. Five-year cumulative estimates of individual radiation exposures were calculated to range from 10 mSv to 642 mSv (median, 61 mSv) resulting from 690 imaging procedures.…”
Section: Roles Of Surveillance Imagingmentioning
confidence: 99%
“…Of these, only 34% of studies were protocol-driven; the remaining studies were optional procedures nearly evenly divided between those for clinical care and surveillance studies. These investigators found that children treated for neuroblastoma had the highest median cumulative exposure to ionizing radiation (214 mSv) but also found that patients treated for lymphoma bore a considerably greater burden (median cumulative exposure of 61 mSv) than patients treated for other malignancies [18]. …”
Section: Roles Of Surveillance Imagingmentioning
confidence: 99%
“…WBMRI identified almost 30% of malignant lesions, more than any other individual screening tool in this study; however, the combination of surveillance elements-clinical examination, bloodwork, and imaging (including brain MRI, abdominopelvic ultrasound, and mammography)-was most instrumental in tumor detection (17). A pilot study screening for osteosarcoma and subsequent malignant neoplasms in hereditary retinoblastoma showed only moderate sensitivity in tumor detection, with limited data for surveillance effectiveness shared by many pediatric tumors (18,38,39). However, as shown by Jasperson and colleagues in comparing WBMRI to biochemical testing in screening for succinate dehydrogenase (SDH)-related tumors, with WBMRI having improved sensitivity and comparable specificity, a high negative predictive of WBMRI has value providing reassurance (19).…”
Section: Who Should Do It?mentioning
confidence: 99%
“…This needs to be balanced against the low positive predictive value from false positive findings, requiring careful consideration as discussed, and PET/MRI may have a role here. International CPS and specific pediatric tumor registries, such as exists for childhood gastrointestinal stromal tumors (GIST), will help provide data that will undoubtedly lead to protocol optimization and rationalization of those CPS in which WBMRI is shown to be most effective (38,40). Further WBMRI protocol modifications will arise from advances in MRI, such as techniques for screening for lung metastases (41).…”
Section: Who Should Do It?mentioning
confidence: 99%